The Effect of Cod Liver Oil and Corn Oil on Platelets and Vessel Wall in Man - Brox, Jan H; Killie, Jan-Eirik; Gunnes, Sigurd; Nordøy, Arne (Thrombosis and Haemostasis, 1981)
Ten healthy male subjects on an ordinary diet were given daily dietary supplement of 25 ml cod liver oil (CLO) or corn oil (CO) for periods of 6 weeks in a crossover study. Significant changes were observed in the plasma total fatty acid composition. The main platelet phospholipids fractions were also significantly altered, particularly by CLO with an increase of the eicosapentaenoic acid (EPA): arachidonic acid (AA) ratio. Both supplements reduced collagen induced platelet aggregation and TXB2 production, with CLO as the most potent one. No spontaneous release of an antiaggregatory substance or 6-keto-PcF1α from vein tissues were found, and the total urinary excretion of prostaglandin metabolites (E and F series) remained unchanged.
Keywords: Cod liver oil; Corn oil; Platelet aggregation; TXB2 formation; Prostacyclin formation